Unilateral Nonconfluent Cluster of Micronodules: Atypical Radiologic Appearance of Pulmonary Tuberculosis in an Immunocompetent Patient - Bushra Johari; Mohammad Hanafiah (Case Reports in Medicine)
Active pulmonary tuberculosis involving the lung parenchyma is typically seen on CT as consolidation, centrilobular nodules with tree-in-bud branching, cavitating lesions, and miliary nodules. However, some atypical CT patterns of granulomatous disease including tuberculosis have been recently described, namely, clusters of nodules without confluence or with confluence. We present a case of a patient who was found to have nonconfluent clusters of micronodules in the right lung with negative sputum culture for tuberculosis. There were also incidental findings of the partial duplex system of the left kidney with mild-to-moderate hydronephrosis in the lower moiety with proximal hydroureter. The urine culture was then positive for mycobacterium tuberculosis; hence, he was commenced on antituberculous medications. A repeated CT scan revealed significant improvement of the aforementioned clusters of micronodules and left hydronephrosis. In the present case, we would like to highlight the atypical appearances of pulmonary tuberculosis in the form of nonconfluent micronodules on HRCT despite negative sputum workup, with the concurrent active genitourinary tuberculosis.